Three Novel Cu(II), Cd(II) and Cr(III) Complexes of 6−Methylpyridine−2−Carboxylic Acid with Thiocyanate: Synthesis, Crystal Structures, DFT Calculations, Molecular Docking and α-Glucosidase Inhibition Studies - Avcı, D.; Altürk, S.; Sönmez, F.; Tamer, Ö.; Başoǧlu, A.; Atalay, Y.; Zengin Kurt, B.Z. (Elsevier Ltd, 2018)
Novel complexes of 6−methylpyridine−2−carboxylic acid and thiocyanate {[Cu(NCS)(6-mpa)2], (1); [Cd(NCS)(6-mpa)]n, (2); [Cr(NCS)(6-mpa)2·H2O], (3)} were synthesized, and their structures were characterized by XRD analysis, FT–IR and UV–Vis spectroscopic techniques. The inhibitory activities of the synthesized complexes (1–3) on α-glucosidase were determined by using genistein reference compound. Furthermore, the optimized geometry and vibrational harmonic frequencies for the complexes 1–3 were obtained by DFT/HSEh1PBE/6–311G(d,p)/LanL2DZ level. Electronic spectral properties were examined by using TD-DFT/HSEh1PBE/6–311G(d,p)/LanL2DZ level with CPCM model. Additionally, major contributions to the electronic transitions were determined via Swizard program. The refractive index, linear optical and non−nonlinear optical parameters of the complexes 1–3 were investigated at HSEh1PBE/6–311G(d,p) level. The docking studies of the complexes 1–3 to the binding site of the target protein (the template structure S. cerevisiae isomaltase are fulfilled. Lastly, natural bond orbital analysis was used to investigate inter- and intra-molecular bonding and interaction among bonds. © 2018 Elsevier Ltd
Keywords: 6−Methylpyridine−2−Carboxylic Acid and Thiocyanate; Docking; FT−IR and UV–Vis; TD/DFT//HSEH1PBE; X−Ray Structure Elucidation; α-Glucosidase Inhibition